Credibility: norwegian students evaluate media studies web sites - Iding, Marie (2006)
This paper investigates Norwegian university students’ evaluations of web site credibility and site authors’ vested interests with respect to a textbased academic site and an informational site with commercial support. Credibility ratings were higher for some aspects of the academic site even though the non-academic sit was rated more highly in presentation design and currency. Negative correlations emerged between academic level and confidence in deciding web site credibility and in detecting misrepresentations.